Pertimbangan Hakim dalam Pemidanaan Anak Pelaku Narkotika: Judicial Reasoning in Sentencing Juvenile Narcotics Offenders - Dhea Aulia; Lelisari Lelisari; Muhammad Khoirul Ritonga (Indonesian Journal of Law and Economics Review, 2026)
General Background: Narcotics crimes constitute a serious legal and social problem that threatens public health and the future of younger generations, including children who are increasingly involved in such offenses. Specific Background: Indonesian criminal law regulates narcotics offenses through Law Number 35 of 2009 and provides special protection for children under Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, requiring judges to consider both juridical and non-juridical aspects. Knowledge Gap: Limited studies have specifically examined judicial considerations in individual court decisions involving juvenile narcotics offenders, particularly in balancing punitive legal provisions with child protection principles. Aims: This study aims to analyze the judicial considerations in Decision Number 14/Pid.Sus-Anak/2025/PN Rap and assess their conformity with narcotics law and juvenile justice principles. Results: The findings indicate that judges based their decision on valid legal evidence, including witness testimony, defendant statements, and forensic results, while also considering the child’s social background, resulting in a sentence of 3 years and 8 months imprisonment in a juvenile facility and 3 months of job training. Novelty: The study demonstrates a combined application of juridical proof and social considerations in judicial reasoning within juvenile narcotics cases. Implications: The findings underline the need for balanced sentencing that integrates legal accountability with rehabilitation and child protection within the juvenile justice system. Highlights• Legal assessment incorporates evidentiary proof and forensic examination in case determination• Social background factors such as family conditions are considered in sentencing decisions• Sanction includes custodial placement and vocational program within juvenile institution KeywordsJuvenile Justice; Narcotics Crime; Judicial Reasoning; Criminal Liability; Child Protection